Morphology of Insects Attracted to Colored Traps in Coffee Plantations in Perangai Village, Lahat Regency - Melanda, Rahmi Bela; Marmaini, Marmaini; Mutiara, Dian (Jurnal Biologi Tropis, 2026)
: A study on the diversity and morphological structure of insects attracted to colored traps in a coffee plantation in Perangai Village, Lahat Regency, was conducted from February to June 2026. Employing a survey approach with purposive sampling, five trap color variations (yellow, green, white, red, and blue) were deployed in the study area. The inventory identified 11 insect species: Oxya chinensis, Valanga nigricornis, Hermetia illucens, Bemisia tabaci, Epilachna sp., Atractomorpha crenulata, Periplaneta americana, Musca domestica, Agelastica alni, Leptocorisa oratorius, and Dysdercus cingulatus. Yellow traps attracted the highest number of insects (90 individuals), followed by green (57), white (47), red (15), and blue (8). Morphological analysis revealed diversity in mouthparts (chewing, sucking, piercing-sucking, biting-chewing), head orientation (hypognathous, prognathous, opisthorhynchous), antennal shapes (filiform, clavate, aristate, pectinate), wing types (membranous, elytra, halteres, hemelytra, tegmina), and leg types (cursorial, saltatorial, raptorial).